Системи візуалізації графічного контенту - Мацовка, Р. Р. (ХНУРЕ, 2024)
This publication considers current issues of graphic content visualization in the context of augmented reality (AR) and compares implementation algorithms using the ARTIVIVE and SparkAR platforms as an example. The work found that using raster images with more contrast pixels helps AR algorithms work better. Comparing the platforms, it is found that SparkAR has an advantage in face recognition and stability of object projection, while ARTIVIVE provides the ability to respond to the change of angle, but has some disadvantages in stability. The study also found issues with the implementation of features on both platforms, such as limitations on facial recognition and file import restrictions. Possibilities for further development of this direction are discussed, including the creation of a platform for working with a timeline and analysis of the impact of online rendering engines on AR work. The work is important for the analysis and improvement of applications for working with augmented reality and can be a starting point for creating your own applications in this field.
Keywords: візуалізація графічного контенту; графічний контент